Comparative Analysis of Textual (Nashiyah) and Contextual (Siyaqiyah) Approaches in Islamic Education - Yondrizal; Edy Juarminson; Tamrin Kamal; Rosniati Hakim; Sri Wahyuni; Md. Ziaur Rahman (Walidem Institute and Publishing, 2025)
Objective: This study aims to compare textual (nashiyah) and contextual (siyaqiyah) approaches in Islamic education, both in terms of basic principles, methods of application, and their implications on the development of students' values and character. Theoretical framework: This study is based on the theoretical framework of Islamic interpretation, which distinguishes between text-based approaches (literal texts) and context-based approaches. Leading figures such as Azyumardi Azra, Fazlur Rahman (with the theory of double movement), and Amina Wadud provide an important foundation in understanding both approaches in the context of education and social religion. Literature review: Previous studies have shown that the textual approach emphasizes the literal and normative meanings of the Qur'an and Hadith, as affirmed by classical scholars such as Ibn Taymiyyah and Al-Ghazali. Meanwhile, the contextual approach considers the social, cultural, and historical background of the revelation of the text, as developed by Fazlur Rahman and Amina Wadud. Methods: This study uses a qualitative approach with an analytical descriptive method. Data were collected through a literature study that involved the analysis of various scientific literature, books, and articles relevant to the theme of textual and contextual approaches in Islamic education. The analysis is carried out systematically to identify the advantages, disadvantages, similarities, and differences between the two approaches. Results: The results of the study show that the textual approach is effective in maintaining the purity of Islamic teachings and providing legal certainty, but it is less adaptive to social changes. In contrast, contextual approaches are more flexible in dealing with the dynamics of the times and relevant to contemporary issues, but are prone to interpretations that deviate from the literal meaning. Both approaches have their respective relevance and effectiveness, and complement each other in Islamic educational practices. Implications: This study encourages proportional integration between textual and contextual approaches in Islamic education to remain normative and responsive to social dynamics. Novelty: This study makes a new contribution by discussing the theoretical and practical comparison of the two approaches in Islamic education and emphasizing the importance of integrating the two as adaptive models in the contemporary era.